Management of children and young people with vision impairment: diagnosis, developmental challenges and outcomes. Issue 6 (16th November 2016) - Keil, Sue; Fielder, Alistair; Sargent, Jenefer
Abstract : Vision impairment (VI) has a significant impact on an individual's ability to engage with everyday tasks. Severe early-onset VI presents different challenges to adult onset visual loss since reduced visual input presents a major obstacle to the acquisition and development of fundamental developmental skills in early and later childhood. Early referral of the child with reduced vision is vital to ensure accurate diagnosis and prompt treatment of any modifiable aspects of the condition. Guidance to ensure optimisation of developmental opportunity through adaptation of play and care is vital from the earliest stages. Cognitive and social challenges occur throughout education and need to be understood and addressed through skilled support. Multiagency input, particularly from health and education, is vital to minimise the risk of adverse outcomes and promote successful transition to independent adulthood. VI may also arise in a variety of neurological disorders, and diagnosis and assessment to ensure appropriate adaptations are made is also crucial for this group of children. This review provides the paediatrician with information on diagnosis, assessment, long-term support needs and outcomes.